A framework for context-aware home-health monitoring. (15th December 2009) - Esposito, Alessandra; Tarricone, Luciano; Zappatore, Marco; Catarinucci, Luca; , Riccardo Colella
This paper presents a proposal for a context-aware framework. The framework is organised according to a general purpose architecture, centred around an ontological context representation. The ontology provides the vocabulary upon which software agents interoperate and perform rule-based reasoning, in order to determine the system response to context changes. Context data are provided by both static and dynamic sources, the core of which is a novel low-cost device enabling the integration of sensor networks with RFID systems. This paper describes system components and their coordinated operations by providing a simple example of concrete application in a home-care scenario.